El Portal 1939-06 (June 1939) - San Jose State College:::Creator::::::::::::
Volume 8. El Portal was a monthly literary magazine published by the English Department featuring student writing. The genres include fiction, poetry, and essays. Issues from May 1933 onwards featured the work of the winners of the Phelan Literary Awards, endowed by a bequest of $10,000 from the late Senator James D. Phelan to San Jose State Teachers College. This is the second incarnation of the literary journal The Quill, which in turn becomes Reed Magazine in 1948.